Anticancer activity of agarwood distillates on lung cancer cells - Hussein, Abeir; Hashim, Yumi Zuhanis Has-Yun; Mohd. Salleh, Hamzah (2015)
Agarwood or gaharu is the fragrant, resinous heartwood that results when some trees, such as Aquilaria malaccensis, are attacked by fungi. Aside from its value as perfume oil, many medicinal claims have been associated with the agarwood itself. This highly-prized heartwood contains a wide array of chemical compounds that fall under various classes of healthy phytochemicals such as terpenoids, alkaloids, and flavonoids. Previous studies have shown promising results when agarwood essential oils were studied for anticancer effects. However, very little information can be found on agarwood distillates, the clear by-products of the agarwood distillation process that possess a characteristic smell, including their therapeutic effects. This paper presents some of the findings in a study of the anticancer activity of agarwood distillates on human lung cancer cells. Two-factor, Face-centred Central Composite Design was used to study the effects of agarwood distillate concentration and time of exposure on attachment (via Trypan blue dye exclusion assay) and cytotoxicity (via MTT assay) of Calu-3 cells cultured in EMEM supplemented with 10% (v/v) FBS. Carried out at three exposure durations (12, 24, and 36 hours), the IC50 values were found to be at concentrations of approximately 20, 80 µL/mL and 150 µL/mL agarwood distillate, respectively, for the Trypan blue dye. The MTT assay yielded IC50 values of approximately 20, 250 µL/mL and 35 µL/mL agarwood distillate, respectively. These results suggest that agarwood distillates possess anti-attachment and cytotoxic effects on Calu-3 lung cancer cells.